Pengembangan Booklet Keanekaragaman Jenis Amphibia Geosite Silahisabungan sebagai Sumber Belajar Keanekaragaman Hayati - Berri Situmorang; Binari Manurung; Melva Silitonga (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to examine the feasibility and effectiveness of a booklet on amphibian species diversity in the Silahisabungan Geosite as a teaching material for biodiversity topics. The research employed a Research and Development (R&D) method using the 4D model, which consists of the Define, Design, Develop, and Disseminate stages. The feasibility of the booklet was evaluated based on expert validation, teacher responses, and student responses, while its effectiveness was assessed through improvements in students’ learning outcomes. Data were collected through interviews, needs analysis questionnaires, booklet validation questionnaires, teacher and student response questionnaires, and cognitive learning achievement tests. The results of the study indicate that: (1) the booklet validation results were categorized as good to very good, with scores of 79.4 from the content expert, 96 from the instructional design expert, and 94 from the graphic design expert; (2) teacher responses were very positive with a score of 96.8, while student responses in individual, small-group, and large-group trials obtained scores of 97.2, 96.2, and 93.75, respectively; (3) the effectiveness test conducted on 27 students showed an N-Gain value of 0.74, classified as high; and (4) the t-test revealed a significant difference between pretest and posttest scores (t = 6.213; p < 0.05). Therefore, the developed booklet is effective in improving students’ cognitive knowledge and is feasible for use as a supplementary teaching material in biodiversity learning.